Analysis of Technologies for the Detection and Diagnosis of Mental Disorders: A Review of the Scientific Literature 2010 – 2020 - Diego Aylas-Lopez; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2021)
Mental disorders manifest themselves in many cases throughout the world. Currently, with the emergence of the Covid-19 pandemic, it has caused a great psychological impact on thousands of people, causing changes in daily life or experiencing for the first time feelings of fear or dread. In this work, a systematic review of the scientific literature was carried out. With the objective of identifying the impact and influence of technologies and their benefits for the detection and diagnosis of this type of disorders. For this purpose, information was searched in different databases such as: ScienceDirect, Scopus, Dialnet, IEEE Xplore, Scielo, Redalyc, EBSCO and Proquest. Thus, a total of 58 articles and scientific journals were collected between 2010 - 2020. The research to be presented has the following structure, which begins with the introduction, where reference is made to the background. Consequently, the methodology will explain the collection of information by applying the criteria for inclusion and exclusion of information from the databases. Then, in the results, we will show with graphs and tables the information that will help us to answer the research questions about technologies to detect and diagnose mental disorders, and also about the factors that alter mental health. So that, in discussion, describe the results found with graphs and tables. And finally, in conclusion, highlighting the results and providing some recommendations for future research.
Keywords: Mental health; mental disorders; Covid-19; technologies; diagnosis; systematic review